Does Work Stressors Lead to Abusive Supervision? A Study of Differentiated Effects of Challenge and Hindrance Stressors - Li Z; He B; Sun X (Psychology Research and Behavior Management, 2020)
Zeying Li,1,2 Bin He,2 Xu Sun2 1School of Computer Information Engineering, Hanshan Normal University, Chaozhou 521000, People’s Republic of China; 2School of Management, Guangdong University of Technology, Guangzhou 510520, People’s Republic of ChinaCorrespondence: Xu SunSchool of Management, Guangdong University of Technology, 161 Ying Long Road, Guangzhou 510520, People’s Republic of ChinaTel +86 158 133 613 64Fax +86 020 870 835 65Email tsunxu@gdut.edu.cnPurpose: From the perspective of affective events theory, the present study examines whether two distinct categories stressors (challenge-hindrance stressors) have different effects (hindrance or promotion) on abusive supervision.Materials and Methods: The data of 203 pairs of supervisor–subordinate have been collected from 12 different Chinese enterprises.We first conducted confirmatory factor analyses (CFA) in Lisrel software to test the model’s validity. And then, we used the descriptive statistics to example the correlations of variables. Finally, we conducted hierarchical regression analysis and bootstrap methods to test hypotheses.Results: The finding shows that two distinct categories stressors have different indirect effects (hindrance or promotion) on abusive supervision. Specifically, challenge stressors reduce abusive supervision through positive affective experience, while hindrance stressors increase abusive supervision through negative affective experience. In addition, locus of control plays a first-stage moderated-mediation role in the indirect effect of challenge stressors on abusive supervision and in the indirect effect of hindrance stressors on abusive supervision.Conclusion: This study offers some comprehensive insights for why and when challenge stressors and hindrance stressors have different effects on abusive supervision. This study extends the current literature by directly testing two different underlying psychological mechanisms (resource acquisition and resource depletion), which are responsible for the different effects of challenge stressors and hindrance stressors. Also, individuals’ cognitive attribution tendency is confirmed as boundary conditions of the direct effect of work stressors on affective experience and indirect effects of work stressors on abusive supervision.Keywords: challenge-hindrance stressors, affective experience, locus of control, abusive supervision, affective events theory